HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK PADA ANAK USIA 12-36 BULAN DI DESA SAMBIREJO, KECAMATAN BRINGIN, KABUPATEN SEMARANG - Selasih Putri Isnawati Hadi (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Background : The quality of a child is seen from his/her growth and development. The early stages of development are vital because they will set and determine the next processes. The developments which need attention are gross motor and fine motor development. Nutritional status is one of the most influencing factors for gross motor and fine motor development especially for 12-36 months years old children. Objectives : The aim of the study is to analyze the association between the nutritional status with the motor development of 12-36 months old children Design : The research used descriptive correlation with the design of cross sectional. The sampling used proportional random sampling technique to 62 samples of 12-36 months old children. Result : Based on the data analysis of nutritional status with gross motor development obtained the Kendal tau p-value=0,000 and p < 0,05 it meant that Ha was accepted so was a correlation between nutritional status with fine motor development. And based on the data analysis of nutritional status with fine motor development obtained the Kendal tau p-value=0,000 and p < 0,05 it meant that Ha was accepted so was a correlation between nutritional status with fine motor development. Conclusion : There was a correlation between nutritional status with motor development of 12-36 months old children. Therefore, the officer of health shall to chek nutritional status and to aplicate the early detection of growth and development child. Keywords : child, nutritional status, gross motor, fine motor Biliographies : 11 (2005-2013)